2012
DOI: 10.1186/1471-2202-13-80
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behaviour of the spinal cord in the transition from quiet stance to walking

Abstract: BackgroundModulation of nociceptive withdrawal reflex (NWR) excitability was evaluated during gait initiation in 10 healthy subjects to investigate how load- and movement-related joint inputs activate lower spinal centres in the transition from quiet stance to walking. A motion analysis system integrated with a surface EMG device was used to acquire kinematic, kinetic and EMG variables. Starting from a quiet stance, subjects were asked to walk forward, at their natural speed. The sural nerve was stimulated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
1
3
2
Order By: Relevance
“…At HO, where an increase of the response was expected for BF and RF (Serrao et al, 2012a), our results showed that neither BF nor RF reflex responses seem to be posture dependent. The modulation on TA can be related to supporting the development of the displacement of the CoP towards the stance leg and the forward movement of the body.…”
Section: Posture Modulationcontrasting
confidence: 58%
See 3 more Smart Citations
“…At HO, where an increase of the response was expected for BF and RF (Serrao et al, 2012a), our results showed that neither BF nor RF reflex responses seem to be posture dependent. The modulation on TA can be related to supporting the development of the displacement of the CoP towards the stance leg and the forward movement of the body.…”
Section: Posture Modulationcontrasting
confidence: 58%
“…In general, previous studies dealing with the relationship between gait and the NWR showed a modulation of the reflex amplitude depending on which moment of the gait process the stimulation was delivered (Spaich et al, 2004(Spaich et al, , 2006Emborg et al, 2009;Serrao et al, 2012a). However, the present study also revealed interactions between postures and stimulation sites in the GIP for the hip and ankle measurements but not for the EMG responses.…”
Section: Posture Modulationsupporting
confidence: 46%
See 2 more Smart Citations
“…Withdrawal reflexes have been used comprehensively in pain research as an index of nociceptive responsiveness in both animal model and human studies (see [25,26] for reviews). Importantly, the reflex is known to be 'modular,' meaning that the organization of the reflex is dependent on site of stimulation [25,27] and phase of the gait cycle during ambulation [28]. The motor response to a noxious stimulus is to withdraw or pull away from the stimulus, which may involve activation of the flexor or extensor musculature, depending on the functional needs of the organism [29].…”
Section: Spinal Hyperexcitabilitymentioning
confidence: 99%